2017
DOI: 10.4172/2155-9880.1000506
|View full text |Cite
|
Sign up to set email alerts
|

A Case of Symptomatic Hypertrophic Cardiomyopathy with Severe Dynamic Gradient

Abstract: Hypertrophic cardiomyopathy is a disease of the myocardium characterized by the thickening of the heart walls. It is a genetic disorder transmitted by first-degree relatives, caused by mutations in genes that code for sarcomere protein.A 77-year-old woman presented to the emergency department and complained of continuous vertigos and presyncope with subsequent fall to the floor with a concussive traumatic brain injury. The ECG observed signs of left ventricular hypertrophy. Blood exams highlighted a slight inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2017
2017
2017
2017

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 15 publications
0
1
0
Order By: Relevance
“…The article published by Piccioni et al [8], reported a case of Hypertrophic cardiomyopathy in a 77-years-old woman. The authors described the process of diagnosis of the condition with the help of ultrasonography and serum troponin expression levels.…”
mentioning
confidence: 99%
“…The article published by Piccioni et al [8], reported a case of Hypertrophic cardiomyopathy in a 77-years-old woman. The authors described the process of diagnosis of the condition with the help of ultrasonography and serum troponin expression levels.…”
mentioning
confidence: 99%